269. Pediatric front to back X-ray chest exposure: Image quality and dose optimization. (December 2018) - Angelini, L.; Mariotti, A.; Santucci, G.; Sanniti, S.; Cavagna, E.; Baldazzi, G.
Abstract : Purpose: In this study we changed the acquisition parameters in chest X-ray of 5 years old pediatric patients in order to lower radiation dose and preserve image quality. A new acquisition technique (T2) was compared to the previous (T1). The comparison regarded dosimetric and a qualitative assessment on phantom and on patients. Methods: For dose evaluation we calculated the ESD on a phantom and on patients and we used PCXMC software to evaluate the effective dose (E). We used the TO.20 Leeds Test and AutoPIA software to perform an analysis on a plexiglass phantom simulating patient with the test in between, exposing the phantom to different parameters in order to choose the best technique to use: T2 and comparing it with T1[1] . The images were analysed from a quantitative viewpoint determining the Correct Observation Ratio% (COR%) and Normalized Correct Observation Ratio% (NCOR%)[2] in order to establish which had the maximum value. For qualitative analysis of the clinical image, radiologists examined X- ray images of patients using T1 and comparing it with T2. Results: We noticed that T2 can entail a lower ESD: −68% and a lower effective dose: −65%. In relation to qualitative analysis, carried out by radiologists, there was no significant preference of one technique over another. T2 proved to be the best also in TO.20 analysis performed on a phantom: COR% is comparable: T2 (36%), T1 (39%) and NCOR% is better: T2 (6.2%), T1 (3.9%). Conclusions: By optimising acquisition parameters in chest acquisition of pediatric patients, using filtration 0.1 mmCu + 1mmAl, removing grid and setting lower kV, it is possible to lower radiation dose preserving image quality.